PERAN JOB CRAFTING SEBAGAI MODERATOR ANTARA PENGGUNAAN TIK DENGAN KETERIKATAN KERJA PADA KARYAWAN GENERASI Z - Adella Trisna Rachmayanti; Rostiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The workforce comprises various generations, each with distinct characteristics, including Generation Z. Known as the “iGen" or internet generation, Generation Z is accustomed to the ease of accessing technology. According to the JD-R model, ICT usage is a work resource and a job demand that can promote work engagement. However, excessive technology use can lead to technostress and burnout. This study examines the role of ICT usage in work engagement and whether job crafting is a mediator to alleviate the pressures associated with ICT usage. This research employed a non-experimental quantitative method with a non-probability sampling technique through purposive sampling. The regression test utilized Moderation Regression Analysis (MRA). The study involved 159 Generation Z employees working in the IT sector. The measurement tools included the Utrecht Work Engagement Scale (UWES-9) by Kristiana et al. (2018), the ICT Resources & Stressor Scale by Cianci et al. (2024), and the Job Crafting Scale (JC-Scale) by Serpara (2023). The results showed that ICT usage contributed to 39.4% of work engagement, while other factors outside the study influenced the remaining percentage. However, job crafting did not act as a moderator in this study. Additional MRA analysis for each dimension of job crafting as a moderator revealed that 2 out of 4 dimensions could function as moderators .